Guidelines of Using the Flipped Classroom in Chemistry Instruction for Upper-Secondary Students with Low Achievement - Sukontorn, Benjaporn; Chittradub, Somphong (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2020)
This research aimed 1) to synthesize the conceptual framework of using the flipped classroom in Chemistry for the low achievement students and 2) to study the results of using Chemistry flipped classroom on learning achievement and instructional satisfaction of the low achievement grade 10 students (Mathayomsuksa 4). The study had 2 steps. Step 1: Selecting research that according to the defined criteria used to synthesize the conceptual framework of using the flipped classroom in Chemistry for the low achievement students. Step 2: Used the conceptual framework of Chemistry flipped classroom to the low achievement students for 4 cycles. The collected data was analized by mean ( ), standard deviation (S.D.) and t-test dependent. The research findings of this study were as follows 1) the flipped classroom steps that synthesized had the appropriate score as 4.78, the highest level. 2) students learned by flipped classroom approach had mean score of the post-test on learning achievement were higher than the pre-test mean score at the significant level of .01 and had high level of satisfaction towards in all 4 cycles.